2015
DOI: 10.1158/1078-0432.ccr-14-0265
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Intermittent Oral Dosing of the Insulin-like Growth Factor-1 and Insulin Receptors Inhibitor OSI-906 in Patients With Advanced Solid Tumors

Abstract: Purpose: We determined the maximum tolerated dose (MTD), safety, pharmacokinetics, pharmacodynamics, and preliminary activity of OSI-906, a potent, oral, dual inhibitor of insulin-like growth factor-1 receptor (IGF1R) and insulin receptor (IR), in patients with advanced solid tumors.Experimental Design: This was a multicenter, open-label, dose escalation phase I study evaluating three intermittent dosing schedules of once-daily OSI-906 [schedule (S) 1, days 1-3 every 14 days; S2, days 1-5 every 14 days; S3, da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 17 publications
3
79
1
Order By: Relevance
“…[15][16][17] Linsitinib (OSI-906) is a potent, oral, small molecule inhibitor of both IGF-1R and IR which has shown preliminary evidence of antitumor activity in a variety of solid tumors, with an acceptable tolerability profile. [18][19][20] Notably, in a dose-finding, phase 1 study, linsitinib resulted in partial responses in two of 15 patients with ACC (79 total study patients). 19 We report here the results of an international phase 3 study evaluating linsitinib in patients with advanced ACC who received at least one but not more than two prior drug regimens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] Linsitinib (OSI-906) is a potent, oral, small molecule inhibitor of both IGF-1R and IR which has shown preliminary evidence of antitumor activity in a variety of solid tumors, with an acceptable tolerability profile. [18][19][20] Notably, in a dose-finding, phase 1 study, linsitinib resulted in partial responses in two of 15 patients with ACC (79 total study patients). 19 We report here the results of an international phase 3 study evaluating linsitinib in patients with advanced ACC who received at least one but not more than two prior drug regimens.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Notably, in a dose-finding, phase 1 study, linsitinib resulted in partial responses in two of 15 patients with ACC (79 total study patients). 19 We report here the results of an international phase 3 study evaluating linsitinib in patients with advanced ACC who received at least one but not more than two prior drug regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Initial trials with monoclonal antibodies as monotherapy were nevertheless disappointing, and further development of these therapies is in question (17,36). To further illustrate this, recent phase I trials of OSI-906 as a single agent demonstrated evidence of clinical benefit (37), and it was speculated that modest coinhibition of the insulin receptor (IR) prevents the relief of a negative feedback loop stimulating tumor growth by elevated insulin levels in vivo (38). In contrast, in a phase III study in patients with adrenocortical carcinoma, a cancer type with frequent IGF2 overexpression, no improvement of overall survival was observed with OSI-906 (39).…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation has been found between a high serum level of IGF-1 and advanced stage of breast cancer (2). Numerous in vitro and in vivo studies have shown that inhibition of IGF-1 signalling decreases tumour growth and metastasis (8).…”
Section: Praca Oryginalnamentioning
confidence: 97%
“…This opens the way for a search for new therapeutic methods, including anti-IGF-1R therapies in female dogs with malignant mammary tumours. Currently, in human medicine studies are being conducted on using anti--IGF-1R inhibitors for therapies of breast cancer (8).…”
Section: Tab 1 Mean ± Sd Concentration Of Igf-1 In Blood Plasma Of mentioning
confidence: 99%